Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Let's solve the given system of equations step-by-step.
The system of equations is:
[tex]\[ \left\{\begin{array}{ll} (1) & 2x - y = 6 \\ (2) & 4x + 2y = 3 \end{array}\right. \][/tex]
### Step 1: Express one of the variables in terms of the other from one of the equations.
Let's take the first equation and solve for [tex]\( y \)[/tex]:
[tex]\[ 2x - y = 6 \implies y = 2x - 6 \][/tex]
### Step 2: Substitute this expression into the other equation.
Now, substitute [tex]\( y = 2x - 6 \)[/tex] into the second equation:
[tex]\[ 4x + 2(2x - 6) = 3 \][/tex]
### Step 3: Solve the resulting equation for [tex]\( x \)[/tex].
Expand and simplify the equation:
[tex]\[ 4x + 4x - 12 = 3 \\ 8x - 12 = 3 \\ 8x = 3 + 12 \\ 8x = 15 \\ x = \frac{15}{8} \][/tex]
### Step 4: Substitute the value of [tex]\( x \)[/tex] back into the equation from step 1 to find [tex]\( y \)[/tex].
Substitute [tex]\( x = \frac{15}{8} \)[/tex] into [tex]\( y = 2x - 6 \)[/tex]:
[tex]\[ y = 2\left(\frac{15}{8}\right) - 6 \\ y = \frac{30}{8} - 6 \\ y = \frac{30}{8} - \frac{48}{8} \\ y = \frac{30 - 48}{8} \\ y = \frac{-18}{8} \\ y = -\frac{9}{4} \][/tex]
### Conclusion
The solution to the system of equations is:
[tex]\[ \left( x, y \right) = \left( \frac{15}{8}, -\frac{9}{4} \right) \][/tex]
So the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] are [tex]\( \frac{15}{8} \)[/tex] and [tex]\( -\frac{9}{4} \)[/tex] respectively.
The system of equations is:
[tex]\[ \left\{\begin{array}{ll} (1) & 2x - y = 6 \\ (2) & 4x + 2y = 3 \end{array}\right. \][/tex]
### Step 1: Express one of the variables in terms of the other from one of the equations.
Let's take the first equation and solve for [tex]\( y \)[/tex]:
[tex]\[ 2x - y = 6 \implies y = 2x - 6 \][/tex]
### Step 2: Substitute this expression into the other equation.
Now, substitute [tex]\( y = 2x - 6 \)[/tex] into the second equation:
[tex]\[ 4x + 2(2x - 6) = 3 \][/tex]
### Step 3: Solve the resulting equation for [tex]\( x \)[/tex].
Expand and simplify the equation:
[tex]\[ 4x + 4x - 12 = 3 \\ 8x - 12 = 3 \\ 8x = 3 + 12 \\ 8x = 15 \\ x = \frac{15}{8} \][/tex]
### Step 4: Substitute the value of [tex]\( x \)[/tex] back into the equation from step 1 to find [tex]\( y \)[/tex].
Substitute [tex]\( x = \frac{15}{8} \)[/tex] into [tex]\( y = 2x - 6 \)[/tex]:
[tex]\[ y = 2\left(\frac{15}{8}\right) - 6 \\ y = \frac{30}{8} - 6 \\ y = \frac{30}{8} - \frac{48}{8} \\ y = \frac{30 - 48}{8} \\ y = \frac{-18}{8} \\ y = -\frac{9}{4} \][/tex]
### Conclusion
The solution to the system of equations is:
[tex]\[ \left( x, y \right) = \left( \frac{15}{8}, -\frac{9}{4} \right) \][/tex]
So the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] are [tex]\( \frac{15}{8} \)[/tex] and [tex]\( -\frac{9}{4} \)[/tex] respectively.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.